Application of System Identification Techniques to Revealing Professional Skills of Teams of Human-Operators. Issue 32 (2016) - Chernyshov, K.R.
Abstract: The paper is devoted to a methodology oriented to eliciting professional skills of a team of human-operators of a technological plant by applying system identification techniques. Within the frameworks, the aim is to derive an input/output model that might reflect the actual level of group professional competences and skills. Deriving the required input/output model is based on applying such a kind of the "proxy", that is indirect, variables as the time. Namely, there is applied the time that is needed to the team of human-operators to make a decision on the plant process behavior using information provided by information sources distributed over an information & control board, such as, say, group view displays (GVD). In turn, these times are proposed to be fixed by use of eye trackers. Obtained in such a manner and calculated by use of data of observation of actual algorithm of experienced human-operator team performance, the model characteristics represent a tool for evaluation of human-operator team experience.